Motion analysis of performance tests using a pulling force device (PFD) simulating a judo throw - Hassmann, M.; Buchegger, M.; Stollberg, K. P.; Sever, A.; Sabo, A. (Procedia Engineering, 2010)
A pulling force device is used to carry out monthly performance tests on 12 judo athletes of the Olympic Center Linz, Austria. The variation of a friction brake simulates the resistance of the opponent in the throwing technique Seoi-Nage. By measuring force and velocity, the parameters are calculated using LabView. A synchronous 3D motion analysis in Peak Motus shows the quality of movement in more detail. The relevant investigations comprise the 3D position of center of mass, ankle and shoulder; knee and elbow angle, body axis as well as trunk rotation.